Numerical investigation of flow in a vertical pipe inlet/outlet with a horizontal anti-vortex plate: effect of diversion orifices height and divergence angle. Issue 1 (1st January 2018) - Gao, Xueping; Zhang, Han; Liu, Jijun; Sun, Bowen; Tian, Ye
ABSTRACT: The vertical pipe inlet/outlet, with a horizontal plate widely used in the pumped storage plant, has the characteristics of complex two-direction flow. The experiment was conducted on the original shape at different discharges. Compared with the experimental results, the current study presents a three-dimension numerical investigation of the turbulent flow in the vertical pipe inlet/outlet using the realizable k-ϵ model. The hydraulic characteristics such as velocity distribution and head losses of the vertical pipe inlet/outlet in different diversion orifices heights and divergence angles have been analysed. The results show that the conditions of pumping mode and generating mode cannot satisfy the optimal hydraulic condition at the same time. Finally, the better value ranges of the diversion orifices height and the divergence angle are proposed taking into account the head losses, the maximum velocity of the diversion orifices and the height of the reverse flow zone.